Determination of Curcuma longa L. (Turmeric) Leaf Extraction Conditions Using Response Surface Methodology to Optimize Extraction Yield and Antioxidant Content. (22nd November 2019) - Kim, Sera; Ko, Seok-Chun; Kim, Yoon-Sook; Ha, Sang-Keun; Park, Ho-Young; Park, Yongkon; Lee, Sang-Hoon
Abstract : Curcuma longa L. (turmeric) has been used as a functional food material, but other parts of it such as leaves are wasted as a byproduct. This work concentrated on developing turmeric leaves as a functional food material by establishing its optimal extraction condition. Response surface methodology was applied to optimize turmeric leaf extraction conditions. Turmeric leaves were pulled out with water and ethanol (10, 30, and 50%). Then, total phenolic compound content, total flavonoid content, and radical-scavenging activity of each extract were quantified to confirm the optimal extracting solvent. According to the results, water was the most efficient solvent to extract antioxidant contents such as total phenolic compounds (3.65 ± 0.02 mg GAE/g) and flavonoids (4.99 ± 0.17 mg QCE/g) content. Radical-scavenging activity was also higher in water extract compared with others such as DPPH (51.10 ± 2.29%), H2 O2 (25.39 ± 2.69%), and ABTS (91.08 ± 0.15%). Central composite design was applied to confirm the effect of independent variables such as temperature ( X 1 ) and time ( X 2 ) to the yield ( Y 1 ). After conducting experiments, the extraction condition was established as 150 min with 1 : 25 ratio at 85°C with a 15.58% yield. Proximate compositions of the extract were determined to suggest background data for further research. In conclusion, this study confirmed the antioxidant property of turmeric leaves and developed the optimal extraction condition of the leaves to promote its application in food industry as a new food source.